Symposium report: emerging threats for human health – impact of socioeconomic and climate change on zoonotic diseases in the Republic of Sakha (Yakutia), Russia. Issue 1 (1st January 2020) - Huber, Irene; Potapova, Katerina; Ammosova, Elena; Beyer, Wolfgang; Blagodatskiy, Sergey; Desyatkin, Roman; Hoelzle, Ludwig E.; Ignateva, Margarita; Kokolova, Ludmila; Lemke, Stefanie; Neustroev, Mikhail; Nyukkanov, Ayan; et al.
ABSTRACT: Population growth, socio-cultural and economic changes as well as technological progress have an immediate impact on the environment and human health in particular. Our steadily rising needs of resources increase the pressure on the environment and narrow down untainted habitats for plants and wild animals. Balance and resilience of ecosystems are further threatened by climate change, as temperature and seasonal shifts increase the pressure for all species to find successful survival strategies. Arctic and subarctic regions are especially vulnerable to climate change, as thawing of permafrost significantly transforms soil structures, vegetation and habitats. With rising temperature, the risk of zoonotic diseases in the Republic of Sakha (Yakutia) has also increased. As vegetation periods prolong and habitats broaden, zoonotic pathogens and their vectors find more favourable living conditions. Moreover, permafrost degradation may expose historic burial grounds and allow for reviving the vectors of deadly infections from the past. To assess the current state of knowledge and emerging risks in the light of the "One Health" concept, a German-Russian Symposium took place on 13 August 2018 in Yakutsk, Russian Federation. This symposium report presents the main findings generated from presentations and discussions.